2023
DOI: 10.1021/acs.nanolett.2c05077
|View full text |Cite
|
Sign up to set email alerts
|

Reversible, Dendrite-Free, High-Capacity Aluminum Metal Anode Enabled by Aluminophilic Interface Layer

Abstract: Aluminum (Al) metal is an attractive anode material for next-generation rechargeable batteries, because of its low cost and high capacities. However, it brings some fundamental issues such as dendrites, low Coulombic efficiency (CE), and low utilization. Here, we propose a strategy for constructing an ultrathin aluminophilic interface layer (AIL) to regulate the Al nucleation and growth behaviors, which enables highly reversible and dendrite-free Al plating/stripping under high areal capacity. Metallic Al can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…2h and i. The calculation results show that graphite possesses lower binding energy (−1.77 eV) than alumina (−1.59 eV), suggesting that the Al nucleation tends to take place on the graphite matrix, 37,38 which is consistent with the experimental result that Al is preferentially plated on the graphite coating rather than the Al substrate.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…2h and i. The calculation results show that graphite possesses lower binding energy (−1.77 eV) than alumina (−1.59 eV), suggesting that the Al nucleation tends to take place on the graphite matrix, 37,38 which is consistent with the experimental result that Al is preferentially plated on the graphite coating rather than the Al substrate.…”
Section: Resultssupporting
confidence: 84%
“…These results indicate that the graphite coating layer greatly impacts the plating/stripping behaviours and improves the electrochemical reversibility of the Al anode. The electrochemical performances of state-of-the-art Al anodes are listed in Table S1 † 10,22,37,39–44 . It is found that our Al-g anode shows competitive electrochemical performances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rechargeable aluminum batteries (RABs) are considered as the promising candidate of state-of-the-art post-lithium battery systems due to the highest abundance, environmental sustainability, low cost, and high theoretical capacity of Al. [1][2][3][4] However, Al anode exhibits poor reversibility and stability of DOI: 10.1002/aenm.202301322 deposition/dissolution caused by parasitic hydrogen evolution reaction, dense passivation layer of Al 2 O 3 , and Al dendrites. [5][6][7] It is urgent to take effective strategies to address these intrinsic drawbacks of Al anodes for their practical deployment.…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous rechargeable zinc ion batteries (ZIBs) are considered among the most promising candidates for the next generation post‐lithium batteries due to their low‐cost, reliable safety, and scalable production [1–6] . Metallic zinc (Zn) as an anode has many inherent advantages such as high specific capacity (820 mAh g −1 ) and volumetric capacity (5857 mAh L −1 ), reasonable redox potential (−0.76 V vs standard hydrogen electrode), and low cost (2.4 USD kg −1 ) [7–9] .…”
Section: Introductionmentioning
confidence: 99%